2017
DOI: 10.1049/mnl.2016.0655
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a nanosilica cross‐linker and investigation of its effect on properties of guar gum fracturing fluid

Abstract: The development of hydraulic fracturing has created a huge demand for fracturing fluids with high performance and low formation damage in recent years. A nanosilica cross-linker precursor (NCP) was prepared by introducing boric acid to the surface of organic silica compound (C 9 H 23 NO 3 Si, a silane coupling agent), the carrier. As-obtained NCP was transformed into nanoparticles (NPs) with a diameter of 10-35 nm by self-aggregation. The resultant NPs were used to crosslink low concentration of guar gum solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The formation of N–B bonds between H 3 BO 3 and KH550 can improve the cross-linking efficiency of TiO 2 nanoparticles onto the polymer chains. 47 , 48 In this process, the dehydration and condensation reaction between the hydroxyl groups Ti–OH and hydroxyl groups of the PVA sponge can enhance the formation of the TiO 2 /PVA nanocomposite. 49 , 50 Besides, the cross-linking reaction of KH550 and H 3 BO 3 can make TiO 2 nanoparticles firmly anchored on the skeletons of the pristine PVA sponge and thus construct rough micro-nanoscale structures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of N–B bonds between H 3 BO 3 and KH550 can improve the cross-linking efficiency of TiO 2 nanoparticles onto the polymer chains. 47 , 48 In this process, the dehydration and condensation reaction between the hydroxyl groups Ti–OH and hydroxyl groups of the PVA sponge can enhance the formation of the TiO 2 /PVA nanocomposite. 49 , 50 Besides, the cross-linking reaction of KH550 and H 3 BO 3 can make TiO 2 nanoparticles firmly anchored on the skeletons of the pristine PVA sponge and thus construct rough micro-nanoscale structures.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the silane coupling agent (KH550) and the TiO 2 –PVA sponge are added to the resulting solution, and the reaction is continued under magnetic stirring. , The silane coupling agent usually acts as a bridge between the H 3 BO 3 cross-linked TiO 2 nanoparticles and the pristine PVA sponge. The formation of N–B bonds between H 3 BO 3 and KH550 can improve the cross-linking efficiency of TiO 2 nanoparticles onto the polymer chains. , In this process, the dehydration and condensation reaction between the hydroxyl groups Ti–OH and hydroxyl groups of the PVA sponge can enhance the formation of the TiO 2 /PVA nanocomposite. , Besides, the cross-linking reaction of KH550 and H 3 BO 3 can make TiO 2 nanoparticles firmly anchored on the skeletons of the pristine PVA sponge and thus construct rough micro-nanoscale structures. Finally, the superhydrophobic/superoleophilic TiO 2 –PVA sponge is obtained by lowering surface energy with an FDTS solution.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of the amount of (NH 4 ) 2 S 2 O 8 , the viscosity of the gel breaking solution decreased and the gel breaking speed was faster, and the gel breaking time of the emulsion fracturing fluid could be adjusted according to the added amount of (NH 4 ) 2 S 2 O 8 . It showed that the emulsion fracturing fluid had good gel breaking properties, the introduction of morpholine heterocycles had little effect on the gel breaking ability of the emulsion fracturing fluid, and the residue content of emulsion fracturing fluid was much lower than the hydroxypropyl guar gum fracturing fluid with residue content of 300–800 mg/L, 33 which reduced the secondary damage to the formation greatly.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al , have prepared three kinds of nano-cross-linking agents using titanium tetrachloride, boric acid, and boron surface-modified alkoxy silicon compounds as modifiers, as well as amine-containing organosilane coupling agent KH550 and nano-SiO 2 as carriers. The main factors affecting the cross-linking time of the cross-linking agent (e.g., material ratio, temperature, reaction medium) were studied, and the structures of the different nano-cross-linking agents were characterized by Fourier transform infrared (FTIR) spectroscopy, laser particle size analysis, and X-ray diffraction (XRD).…”
Section: Application Of Nanotechnology In Hydraulic Fracturing Of Unc...mentioning
confidence: 99%